Migration Degree of Selected Mycotoxins in the Distillation Process and Their Determination in Distilled Spirits from Pilot-Scale Continuous Distillation - Jung-Ah Shin; Ki-Teak Lee (Foods, 2023)
Mycotoxins (ochratoxin A (20 ppb), aflatoxin B1 (40 ppb), deoxynivalenol (4 ppm), and zearalenone (800 ppb)) were intentionally added to rice bran raw materials. After fermentation, their contents were determined in the distillate and distillery stillage obtained using single-stage and continuous pilot plant-scale columns. After single-stage distillation, aflatoxin B1, deoxynivalenol, and zearalenone were not detected in the distillate, indicating that even if a certain amount (four times the maximum residue limit (MRL)) was present in the raw material, it would not remain in the distillate after fermentation and distillation. Most mycotoxins remained in the distillery stillage, and their residual rates ranged from 54.0–96.2%. For ochratoxin A, 0.19 ppb was found in the distillate and this migration occurred in three consecutive distillations (0.11–0.22 ppb). Ochratoxin A and aflatoxin B1 were not detected in the distillate (alcohol content 93.9% and 95.4%, respectively) obtained from the contaminated fermented liquid (approximately three times the MRL based on the raw material) using the pilot-plant scale continuous distillation column. Therefore, the migration of mycotoxins is difficult when the distilled spirit is produced using a continuous distillation column, even if the raw material is contaminated with certain amounts of the investigated mycotoxins.